“El balance social y su incidencia en la toma de decisiones en la Cooperativa de Ahorro y Crédito ANDINA Ltda. periodo 2021 – 2022” - Del Pezo Rosales, Marlys Fiorella (2024)
The main objective of this research was to analyze the components of the Social Balance with a managerial approach that contributes to decision-making. The methodology used as the application of a questionnaire aimed at the entity's internal and external users to evidence and analyze the impact and implementation of this management tool. The results obtained from the comparison of the Social Balance of the periods 2021 and 2022 showed that the Cooperativa de Ahorro y Credito Andina Ltda., presents deficiencies with respect to five macro dimensions, therefore significant percentages were evidenced in different indicators that represent the variance of the same, therefore, voluntary and open association, democratic control of the members, Training and information, economic participation of members and cooperation between cooperatives, depending on the weakness and their area of greatest incidence, must improve this aspect for their future. Once those deficiencies were identified, an improvement plan was designed, since in this way, when implemented, operations will be optimized, it will strengthen its financial position and thus offer a better service to its partners, among the most relevant action plans is specified the development of strategies for revenue generation, cost and process analysis, Design of training programs and analysis of the interest rate structure.